2009
DOI: 10.1080/01421590802650142
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to patient safety amongst medical students and tutors: Developing a reliable and valid measure

Abstract: Background: Patient safety education is an increasingly important component of the medical school curricula. Aims: This study reports on the development of a valid and reliable patient safety attitude measure targeted at medical students, which could be used to compare the effectiveness of different forms of patient safety education delivery. Methods: The Attitudes to Patient Safety Questionnaire (APSQ) was developed as a 45-item measure of attitudes towards five patient safety themes. In Study 1, factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 21 publications
8
107
1
6
Order By: Relevance
“…In the few PHCC with a high number of patients attending topic. WHO Patient Safety Curriculum Guide: Multiand work overload, participants showed that a shorter shift professional Edition seeks to fill the gap in patient safety for the doctors and taking breaks would reduce medical education by providing a comprehensive curriculum 8 error .These findings agree with those reported in 2009 by designed to build foundation knowledge and skills for all 7 Carruthers et al Teachers in this study did not agreed that health-care students that will better prepare them for shorter shift will reduce errors(mean score is 2.47).But they 4 clinical practice in a range of environments .This agreed that number of hours doctors work increases the curriculum guide provides 11 ready to teach patient safety likelihood of medical errors. topic.…”
Section: Error Inevitabilitysupporting
confidence: 80%
“…In the few PHCC with a high number of patients attending topic. WHO Patient Safety Curriculum Guide: Multiand work overload, participants showed that a shorter shift professional Edition seeks to fill the gap in patient safety for the doctors and taking breaks would reduce medical education by providing a comprehensive curriculum 8 error .These findings agree with those reported in 2009 by designed to build foundation knowledge and skills for all 7 Carruthers et al Teachers in this study did not agreed that health-care students that will better prepare them for shorter shift will reduce errors(mean score is 2.47).But they 4 clinical practice in a range of environments .This agreed that number of hours doctors work increases the curriculum guide provides 11 ready to teach patient safety likelihood of medical errors. topic.…”
Section: Error Inevitabilitysupporting
confidence: 80%
“…Thirty-three (34.7%) of the 95 factor analyses included all factor loadings for all items, making clear to the reader the distribution of items across factors. For example, Carruthers and colleagues 34 reported in their study that the item "All medical errors should be reported" loaded on the factor named "disclosure responsibility." Thirty (31.6%) analyses reported only factor loadings for items that met a certain criterion, but 32 (33.7%) reported no factor loadings.…”
Section: Rotation Methodmentioning
confidence: 97%
“…Standardized instruments for the assessment of patient safety culture are mainly catered for health care personnel such as clinicians and managers (Romano et al 2009). A valid instrument targeted at medical students has recently been developed but unfortunately had not come to our attention earlier (Carruthers et al 2009). The follow-up period in this study was short and we were only able to assess short-term impact.…”
Section: Patient Safety For Medical Studentsmentioning
confidence: 99%